2017
DOI: 10.1089/jpm.2017.0065
|View full text |Cite
|
Sign up to set email alerts
|

How Often Is End-of-Life Care in the United States Inconsistent with Patients' Goals of Care?

Abstract: One in eight respondents stated care in the last months of life was inconsistent with patients' wishes; such care was associated with worse ratings of care, pain management, and communication with clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 9 publications
1
76
1
Order By: Relevance
“…27 Even though individuals may differ in their preferences regarding location of death, the ongoing trend toward stabilization of ICU use is an important marker of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…27 Even though individuals may differ in their preferences regarding location of death, the ongoing trend toward stabilization of ICU use is an important marker of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that, when compared with caregivers who reported goalconcordant care, those reporting goal-discordant care rated the quality of communication and quality of care lower. 82 Limitations of this approach include the potential for multiple biases [83][84][85] and challenges identifying surrogates. However, the Veterans Affairs administration's Bereaved Family Survey 86 and several mortality follow-back studies have demonstrated the feasibility of this approach.…”
Section: Goal-concordant Carementioning
confidence: 99%
“…The Veterans Affairs Bereaved Family Survey uses such a measure and research instruments, including the National Health and Aging Trends Study, and multiple mortality follow-back studies have used this approach. 27,51,52 A recent review of goal-concordance measurement promoted this approach. 49 Still, while it can be incorporated into bereavement surveys, response rates of such surveys have been low in some settings 13 and do not reflect the perspective of the patient himself/herself.…”
Section: Challenges Recommendations and Future Researchmentioning
confidence: 99%